2018
DOI: 10.22159/ijap.2018v10i4.24916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymers on the Physicochemical and Drug Release Properties of Transdermal Patches of Atenolol

Abstract: Objective: The objective of this research work was to develop a transdermal drug delivery system containing atenolol with different ratios of hydrophilic and hydrophobic polymeric combinations, using solvent evaporation technique and to examine the effect of hydrophilicity and hydrophobicity of polymers on the physicochemical and drug release properties of transdermal patches.Methods: Solvent casting method has been used to formulate transdermal patches. Hydroxypropyl methylcellulose (HPMC), Polyvinylpyrrolido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Tensile strength = 0.329917+0.000540* HPMC 50 cps-0.000088* Ethylcellulose+0.004556* Almond oil. [15]. The linear equation generated by the software is given below:…”
Section: Resultsmentioning
confidence: 99%
“…Tensile strength = 0.329917+0.000540* HPMC 50 cps-0.000088* Ethylcellulose+0.004556* Almond oil. [15]. The linear equation generated by the software is given below:…”
Section: Resultsmentioning
confidence: 99%
“…An optimum proportion of hydrophilic and hydrophobic polymer was required to prepare effective transdermal patches. 22 Mahdie Torkaman et al, (2017) 33 observed that there were considerable numbers of medicines that cannot be dissolved in water or had a little aqueous solubility, which caused problems in their absorption and reduction of bioavailability of them subsequently. Various methods have been developed to increase the solubility of drugs to treat these problems.…”
Section: Usingmentioning
confidence: 99%
“…Accurately weighed 10 mg of drug was dissolved in 10 ml of 7.4 pH buffer solution in 10 ml of volumetric flask (Kumar et al 2018). The resulted solution 1000μg/ml and from this solution 1 ml pipette out and transfer into 10 ml volumetric flask and volume make up with 7.4 pH buffer solution prepare suitable dilution to make it to a concentration range of 5-25 μg/ml.…”
Section: Determination Of λMax Of Tazarotenementioning
confidence: 99%